If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(y + 3) + 4(3y + -5) = 6(y + -6) + 11 Reorder the terms: -5(3 + y) + 4(3y + -5) = 6(y + -6) + 11 (3 * -5 + y * -5) + 4(3y + -5) = 6(y + -6) + 11 (-15 + -5y) + 4(3y + -5) = 6(y + -6) + 11 Reorder the terms: -15 + -5y + 4(-5 + 3y) = 6(y + -6) + 11 -15 + -5y + (-5 * 4 + 3y * 4) = 6(y + -6) + 11 -15 + -5y + (-20 + 12y) = 6(y + -6) + 11 Reorder the terms: -15 + -20 + -5y + 12y = 6(y + -6) + 11 Combine like terms: -15 + -20 = -35 -35 + -5y + 12y = 6(y + -6) + 11 Combine like terms: -5y + 12y = 7y -35 + 7y = 6(y + -6) + 11 Reorder the terms: -35 + 7y = 6(-6 + y) + 11 -35 + 7y = (-6 * 6 + y * 6) + 11 -35 + 7y = (-36 + 6y) + 11 Reorder the terms: -35 + 7y = -36 + 11 + 6y Combine like terms: -36 + 11 = -25 -35 + 7y = -25 + 6y Solving -35 + 7y = -25 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. -35 + 7y + -6y = -25 + 6y + -6y Combine like terms: 7y + -6y = 1y -35 + 1y = -25 + 6y + -6y Combine like terms: 6y + -6y = 0 -35 + 1y = -25 + 0 -35 + 1y = -25 Add '35' to each side of the equation. -35 + 35 + 1y = -25 + 35 Combine like terms: -35 + 35 = 0 0 + 1y = -25 + 35 1y = -25 + 35 Combine like terms: -25 + 35 = 10 1y = 10 Divide each side by '1'. y = 10 Simplifying y = 10
| -10(z+3)+4(4z-4)=5(z-5)+12 | | -z+5z=6z-8+7z | | 4x+4=-20 | | -7+x=12 | | 4x-2=4x-2 | | 2x+10=38 | | 4x+1=21+2x | | x*x+2x+1=0 | | 9x+4=3x-9 | | 4x+6x=5(6) | | 7x-14=18-4x | | 17+3x=-3 | | 3(x+3)=15 | | 18-14x= | | 8x-3=21 | | -11-5a=6(5a+4) | | 8(1+5x)+5=13+5x | | -8(-8x-6)=-6x-22 | | -8(-8x-6)=-9x-22 | | -5n-8(1+7n)=-8 | | 10(1+3b)=-20 | | 8=8v-a(v+8) | | -6(1-5v)=54 | | -2=-(n-8) | | 4(-x+4)=12 | | -13=5(1+4m)-2m | | 37=-3+5(x+6) | | 18=3(3x-6) | | 42=8m+13m | | -14v+14v=-10 | | 6r-1+6r=11 | | 4x+6+3=17 |